Analysis of Midwifery Quality Service In Primary Health Care - Asti Nurhayati; Dinda Nur Wijayanti (Syntax Corporation, 2022)
Background: Midwifery quality service affect to quality satisfaction level and lead to a decreasing maternal mortality rate and infant mortality rate in Indonesia. Midwifery service is mostly delivered in primary health care. Therefor it is important to analyse the quality of midwifery service. Methode: A cross sectional survey, conducted in 6 primary health care and involving 75 respondents. Two questionaire were used to measure perceptions of midwifery quality service and quality satisfaction level. Result: The results showed the quality of midwifery services affected the level of service satisfaction by 2.8%. The majority of respondents felt that the midwifery service they received was satisfying as many as 39 respondents (52%). However the majority of (92%) in antenatal care the respondents stated their dissatisfaction in antenatal care service. This is caused by communication factors between midwives and patients. Conclusion: Many respondents stated that communication by midwives was still poor. This is caused by several factors including due to personal needs, internal communication factors, and patient service factors at the primary health care. This can be seen from the many respondents who gave an not qualified response to item reliability on the variable quality of midwifery services.